A multi‐method investigation of temperature, moisture and salt dynamics in tafoni (Tafraoute, Morocco). Issue 4 (14th October 2015) - Schnepfleitner, Harald; Sass, Oliver; Fruhmann, Stefanie; Viles, Heather; Goudie, Andrew
Abstract: Despite numerous investigations and theoretical models, tafoni weathering is still not fully understood largely because of limited data available on temperature, moisture and salt regimes. We investigated tafoni developed in granite in the Tafraoute region, Morocco, through an exploratory, two‐week multi‐method field campaign. Temperatures were measured with iButtons and by means of infrared thermography; moisture distribution and progress were captured with handheld moisture sensors and with drilled‐in iButtons. Salts were analysed in drill dust samples from different positions and rock depths. The results derived from very different techniques mutually support one another. Salts and moisture are concentrated near the base of the investigated tafoni, probably due to a saturated pore water body around the base of rock tors. Salts are accumulated close to the rock surface in tafoni, but not on the surrounding rock surfaces. A clear correlation was found between moisture and salt contents. Within a tafone, areas of higher humidity also display increased salt concentration near the surface. The temperature/humidity records allied with ionic analyses suggest that sodium sulfate dominates and is likely to undergo frequent phase changes from thenardite to mirabilite and vice versa. Two pathways of salt transport in and around tafoni are assumed based on the data: infiltration with rainfall on the top and around tors and boulders, and capillary rise from saturated pore water bodies to the surface. Copyright © 2015 John Wiley & Sons, Ltd.